Efficient one-pot tandem catalysis of glucose into 1, 1, 2-trimethoxyethane over W-Beta catalysts. Issue 4 (21st January 2022) - Zhao, Xinpeng; Liu, Wang; Zhu, Lijun; Zhang, Yanfei; Sun, Mengya; Miao, Gai; Luo, Hu; Li, Shenggang; Kong, Lingzhao
Abstract : 1, 1, 2-Trimethoxyethane was synthesized from glucose over W-Beta catalysts with a high yield of 54.2% through epimerization, RAC, acetalization, and etherfication processes. Abstract : One-pot efficient transformation of glucose into 1, 1, 2-trimethoxyethane via epimerization, retro-aldol condensation (RAC), acetalization, and etherification processes over W-Beta catalysts in the methanol phase was proposed. Uniform dispersive 0.5 wt% tungsten species stabilized by the silanol nests of the Beta zeolite support led to a high 1, 1, 2-trimethoxyethane (C5 H12 O3 ) yield of 54.2% at 200 °C, 4.0 MPa N2, and 4.0 h. The medium Lewis acid arising from the framework W 5+ facilitated the glucose epimerization and RAC reaction while effectively inhibiting the glucose isomerization into fructose, meanwhile, the weak Brønsted acid derived from the residual silanol nests served as the active site for the etherification. The novel reaction pathway from glucose to 1, 1, 2-trimethoxyethane through C4 and C2 intermediates was also proposed.